Computed Tomography Appearance of Normal Nonossified Thyroid Cartilage. Issue 2 (March 2015) - Dadfar, Nazanin; Seyyedi, Mohammad; Forghani, Reza; Curtin, Hugh D.
<x xml:space="preserve">Abstract</x> Objective The objective of this study was to determine the density and homogeneity of the nonossified thyroid cartilage (NOTC) on contrast-enhanced computed tomography (CT) providing preliminary information for future evaluation of cartilage invasion using dual-energy CT. Methods One hundred normal-larynx CT scans were evaluated for the density and homogeneity of NOTC. Results The density of the NOTC was homogeneous in all cases. Nonossified thyroid cartilage had higher mean density than contiguous muscle, but there was overlap. In 47 cases, a lucent area was observed at the junction of the ossified and NOTC but not within the NOTC itself. In 11 cases, ossification was observed in only 1 cortex of the thyroid cartilage. Cartilage at the anterior commissure was not ossified in 7 cases. Conclusions Nonossified thyroid cartilage has a homogeneous appearance on contrast-enhanced CT scans, but showed some normal variations that could be mistakenly reported as tumor invasion.